An Analytic Method for the Kinematics and Dynamics of a Multiple-Backbone Continuum Robot. (31st January 2013) - He, Bin; Wang, Zhipeng; Li, Qiang; Xie, Hong; Shen, Runjie
Continuum robots have been the subject of extensive research due to their potential use in a wide range of applications. In this paper, we propose a new continuum robot with three backbones, and provide a unified analytic method for the kinematics and dynamics of a multiple-backbone continuum robot. The robot achieves actuation by independently pulling three backbones to carry out a bending motion of two-degrees-of-freedom (DoF). A three-dimensional CAD model of the robot is built and the kinematical equation is established on the basis of the Euler-Bernoulli beam. The dynamical model of the continuum robot is constructed by using the Lagrange method. The simulation and the experiment's validation results show the continuum robot can exactly bend into pre-set angles in the two-dimensional space (the maximum error is less than 5% of the robot length) and can make a circular motion in three-dimensional space. The results demonstrate that the proposed analytic method for the kinematics and dynamics of a continuum robot is feasible.